The Effect of Garlic (Allium sativum) Water Extract in Drinking Water on Physical Quality of Egg Lohmann Brown Laying Hens Aged 22-30 Weeks - W., Nanda; Bidura, I G. N. G.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The purpose of this study is to determine the extent of the effect of  garlic ( Allium sativum ) on physical quality of eggs lohmann brown age 22-30 weeks. This research was conducted for 3 months at laying hens farm in Dajan Peken Village, Tabanan Sub-district, Tabanan Regency. 36 Lohmann Brown chickens with homogeneous weights were kept in 18 plots of batrey cages. The design used in this study was a complete randomized design (CRD) with 3 treatments and 6 replications. The treatment consisted of drinking water without added garlic water extract (A) as control, drinking water with 3% extra garlic water extract (B) and drinking water with additional garlic water extract of 6% (C). The variables observed in this study were egg weight, percentage of egg white to egg weight, egg yolk percentage to egg weight, and percentage of egg shell to egg weight. The results showed the egg weight, egg yolk percentage and egg shell percentage in chicken has given garlic water extract was significantly heavier (P <0.05) compared with the controls, while in actual egg white percentage (P> 0.05) smaller than control. Based on the result of this research, it can be concluded that the giving of garlic extract (Allium sativum) with 3% and 6% level through the drinking water can increase egg weight, egg yolk percentage, and egg shell percentage, and decrease percentage of chicken egg white Lohmann Brown age 22-30 weeks. Keywords: garlic, Lohmann Brown, egg quality,